2007
DOI: 10.1097/grf.0b013e31804bdec4
|View full text |Cite
|
Sign up to set email alerts
|

Elective Induction: When? Ever?

Abstract: The frequency of labor induction has increased significantly in recent years. Although medically indicated inductions comprise a portion of this increase, elective inductions have increased in frequency as well. Given that elective inductions, by definition, provide no benefit from a strictly medical standpoint, it is particularly important to evaluate whether women who undergo these inductions incur greater risks than those who labor spontaneously. This article will assess whether elective inductions are asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 25 publications
0
17
1
2
Order By: Relevance
“…By definition this intervention confers no clear medical benefit and rigorous evaluation of the associated maternal and neonatal outcomes is warranted. 5 Our understanding of these outcomes is influenced by flawed methodology of older observational studies and the inherit limitations of contemporary nonrandomized studies. [6][7][8] Cesarean delivery rate is the outcome most significantly affected by a flawed control group-spontaneous labor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By definition this intervention confers no clear medical benefit and rigorous evaluation of the associated maternal and neonatal outcomes is warranted. 5 Our understanding of these outcomes is influenced by flawed methodology of older observational studies and the inherit limitations of contemporary nonrandomized studies. [6][7][8] Cesarean delivery rate is the outcome most significantly affected by a flawed control group-spontaneous labor.…”
Section: Methodsmentioning
confidence: 99%
“…15 In light of these uncertainties, practice patterns typically follow commentaries and expert opinions that limit elective inductions before 41 weeks of gestation to research protocols, particularly in nulliparous women with an unfavorable cervix until this pregnancy management strategy is better studied. [4][5][6] The purpose of this study is to describe the effect of elective induction of nulliparous women at 39 weeks of gestation with a Bishop score 5 or less on cesarean delivery rates.…”
Section: Methodsmentioning
confidence: 99%
“…Half of cesarean sections for dystocia in induced labor were performed before 6 cm of dilation, suggesting that clinical impatience may play a role in decision-making. Some studies also suggest that induction of labor increases the risk of postpartum hemorrhage and blood transfusion 22. Therefore, while more research is warranted, caution is needed to perform elective labor induction, as it may result in maternal morbidity and repeat cesarean deliveries in subsequent pregnancies.…”
Section: Commentsmentioning
confidence: 99%
“…Grobman [14] has also concluded that there is an increased risk of adverse neonatal outcome and caesarean sections rate in elective deliveries before completion of 39 weeks. These studies confirm the wisdom of the recommendations of professional bodies such as the American College of Obstetricians and Gynaecologists and their British and Canadian counterparts.…”
Section: Discussionmentioning
confidence: 99%